Supplementation of corn oil Ω-6 fatty acids in feed for reproduction performance of threadfin rainbowfish Iriatherina werneri Meinken, 1974 - Rahmadani Rahmadani; Mia Setiawati; Dinar Tri Soelistyowati (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2019)
Rainbow fish (Iriatherina werneri) is a type of partial spawner fish with the little number of eggs production. The high contain of essential fatty acid (Linoleic acid 18:2 Ω-6) in corn oil was widely used as a source of fatty acid in the broodstock feed. The aim of this study was to evaluate the additional of LA fatty acid in feed for reproduction performance of rainbow fish. This study used a complete random design consists of three treatments and six replicates with different doses of corn oil LA in feed, Ω-6 0%, Ω-6 1%, and Ω-6 2%. Rainbow fish broodstock as sampel test with body weight 0.10-0.18g for females 0.21 ± 0.001 g, were kept separately in each tanks (size 30 cm x 30 cm x 30 cm) with density 15 fish per tanks. Broodstock were given diet three times daily at 08:00 am, 12:00 am and 17:00 pm by at satiation. The trial feed was administrated for 30 days before conducted the mass spawning for seven days with ratio of the male and female broodstock was 1:3. The results showed that treatment without supplementation of Ω-6 corn oil performed highest number of eggs 290 ± 125, hatching rate 55,99 ± 14,80%, survival rate 8,43% and the proportion of vitellogenic cell was more dominant, but the best of larval performance was observed in tretament of Ω-6 1% of highest larval length 3.00 mm and 100% percentage of normal larvae. It can be concluded that the supplementation of 1 % the Ω-6 fatty acid corn oil in the feed to produce reproductive performance was supported by the results of the histology of the eggs and larvae of the best performance in rainbowfish. Abstrak Ikan pelangi (Iriatherina werneri) tergolong jenis ikan pemijah bertahap dengan jumlah telur yang dihasilkan relatif sedikit. Kandungan asam lemak esensial linoleat (18:2Ω-6) yang tinggi dalam minyak jagung banyak digunakan sebagai sumber asam lemak pada pakan induk. Penelitian ini bertujuan untuk mengevaluasi penambahan asam lemak linoleat Ω-6 minyak jagung dalam pakan terhadap kinerja reproduksi ikan pelangi. Penelitian menggunakan rancang-an acak lengkap yang terdiri atas tiga perlakuan dan tiga ulangan yaitu dosis penambahan asam lemak Ω-6 minyak jagung dalam pakan n-6 0%, n-6 1% dan n-6 2%. Ikan uji yang digunakan adalah induk ikan pelangi betina dengan kisaran bobot 0,10-0,18 g dan induk jantan 0,21±0,001g, dipelihara secara terpisah di akuarium berukuran 30 cm x 30 cm x 30 cm dengan padat tebar 15 ekor per akuarium. Ikan diberi pakan uji dengan frekuensi tiga kali dalam sehari yaitu pada pukul 08.00, 12.00 dan 17.00 secara at satiation. Pakan perlakuan diberikan selama 30 hari kemudian dilakukan pemijahan secara massal selama tujuh hari dengan perbandingan induk jantan dan betina 1:3. Hasil pene-litian menunjukkan bahwa perlakuan tanpa penambahan Ω-6 minyak jagung menghasilkan jumlah telur 290±125 butir, derajat penetasan telur 55,99±14,80%, sintasan 8,43% tertinggi serta proporsi vitellogenic cell yang lebih dominan, namun performa larva terbaik diperoleh pada perlakuan Ω-6 1% dari panjang larva tertinggi 3,00 mm dan persentasi larva normal 100%. Disimpulkan bahwa penambahan 1% asam lemak Ω-6 minyak jagung dalam pakan menghasilkan performa reproduksi yang didukung oleh hasil histologi telur serta performa larva yang terbaik pada ikan pelangi.